Optimizing Digital Applications For MSMEs In Operational Efficiency And Encouraging The Acceleration Of The Digital Economy - Eka, Andi Primafira Bumandava; Sari , Sarlina; Sutono, Sutono; Tamzil , Fachmi; Anggraeni , Dewi (Jurnal Ekonomi, 2024)
In the digital economy era, the application of information and communication technology is the main support for MSMEs to improve operational efficiency. This study uses a systematic literature review method to review and analyze literature related to the adoption of digital technology in MSMEs. The results show that digital applications such as inventory management systems, e-commerce platforms, digital marketing tools, and financial applications can significantly improve the operational efficiency of MSMEs. However, the adoption of these technologies still faces barriers such as limited resources, lack of technical knowledge, and minimal infrastructure support. To encourage the adoption of digital technology, it is necessary to improve digital literacy, financial support, and strengthen infrastructure. Case studies show the success of MSMEs that have adopted digital technology in increasing sales and operational efficiency. This research provides practical recommendations for MSMEs, government, and other stakeholders in supporting MSME digitalization, which in turn is expected to contribute to the acceleration of the digital economy in Indonesia.